A Single 60.000 IU Dose of Erythropoietin Does Not Improve Short-Term Aerobic Exercise Performance in Healthy Subjects: A Randomized, Double-Blind, Placebo-Controlled Crossover Trial - Haider, Thomas; Diaz, Victor; Albert, Jamie; Alvarez-Sanchez, Maria; Thiersch, Markus; Maggiorini, Marco; Hilty, Matthias P.; Spengler, Christina M.; Gassmann, Max (Frontiers in Physiology, 2020)
Erythropoietin (EPO) boosts exercise performance through increase in oxygen transport capacity following regular administration of EPO but preclinical study results suggest that single high dose of EPO also may improve exercise capacity. Twenty-nine healthy subjects (14 males/15 females; age: 25 ± 3 years) were included in a randomized, double-blind, placebo-controlled crossover study to assess peak work load and cardiopulmonary variables during submaximal and maximal cycling tests following a single dose of 60.000 IU of recombinant erythropoietin (EPO) or placebo (PLA). Submaximal exercise at 40%/ 60% of peak work load revealed no main effect of EPO on oxygen uptake (27.9 ± 8.7 ml min-1·kg-1/ 37.1 ± 13.2 ml min-1·kg-1) versus PLA (25.2 ± 3.7 ml min-1·kg-1/ 33.1 ± 5.3 ml min-1·kg-1) condition (p= 0.447/ p= 0.756). During maximal exercise peak work load (PLA: 3.5 ± 0.6 W·kg-1 vs. EPO: 3.5 ± 0.6 W kg-1, p= 0.892) and peak oxygen uptake (PLA: 45.1 ± 10.4 ml·min-1 kg-1 vs. EPO: 46.1 ± 14.2 ml·min-1 kg-1, p= 0.344) reached comparable values in the two treatment conditions. Other cardiopulmonary variables (ventilation, cardiac output, heart rate) also reached similar levels in the two treatment conditions. An interaction effect was found between treatment condition and sex resulting in higher peak oxygen consumption (p= 0.048) and ventilation (p= 0.044) in EPO-treated males. In conclusion, in a carefully conducted study using placebo-controlled design the present data failed to support the hypothesis that a single high dose of EPO has a measurable impact on work capacity in healthy subjects.